Chaotic encryption scheme for double grayscale images using Sprott B hyperchaotic map - Syahidatul Shafiqah Ramlee (Semarak Ilmu, 2024)
Image encryption become more significant since most of our data are communicated and stored as digital image form. To warrant high confidentiality, cipher image must be the produced in excellent quality to avoid any information leakage related to the original image. Since image has become one of the most used tools in information exchanges, large production and storage of cipher images are highly demanded, and this scenario could affect the production of high-quality cipher images. While most of existing encryption for images are for single image, processing multiple images simultaneously comes in handy as a fitting fast action to realize the convenience of encryption, storage, and transmission of multiple images. Inspired by those idea, we proposed a new chaotic encryption scheme using Sprott B hyperchaotic map. Using this scheme, two grayscale images are encrypted to produce a single cipher image. The encryption begins with the process of combining two images and encrypting the combined image using the hyperchaotic map. One cipher image will be produced representing and carrying information of the combination of the two images. Our experiments demonstrated significant enhancement offered by the scheme, while maintaining the quality of the recovered plain image. The proposed scheme yields cipher image with excellent quality in terms of noise-like visual of which the information of the images is concealed. While the proposed scheme satisfies the requirements of producing cipher images with excellent quality, it also achieves the credibility to decrypt the cipher image and restoring the plain image exactly similar to the original image.